Beyond the surface: a color-inclusive guide to central line site assessment - Meredith Herrera; Siobhan Eichenblat; Eileen Campbell; Julia Shick; Heather Brown; Chelsea Brinkley; Shelley Kester; Jessica Layell; Catherine L Passaretti; Mindy M Sampson (Cambridge University Press, 2024)
Significant gaps exist in representation of diverse populations in central-line assessment education and tools. We review some of these gaps and provide some real-world guidance on how to assess central line sites in patients of all skin tones.